ANALISIS KECEPATAN ALIRAN LAHAR GUNUNG MERAPI BERDASARKAN DATA REAL-TIME SEISMIC AMPLITUDE MEASUREMENT (RSAM) TAHUN 2011 - , ATIN LELYA S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Real-time Seismic Amplitude Measurement is the average of absolute seismic amplitude measured in a certain time interval. This method can be used for lahars monitoring which was applied in Merapi Volcano. The data acquisition was done in 2011 around eight rivers i.e. Kali Boyong, Kali Putih, Kali Senowo, Kali Gendol, Kali Opak, Kali Lamat, Kali Kuning, and Kali Krasak, using 14 observation stations. The headwaters of the rivers are on the Merapi volcano slope. Lahars event was determinated from RSAM value, recording time, and graphic pattern. We got 10 lahars events i.e. 7 lahars events in Kali Boyong, 2 lahars events in Kali Putih, and 1 lahar event in Kali Senowo. Correlation graph of two lahars event graph was used to determine the time difference between two observation stations of lahars event. Lahars flow velocity analysis methods used correlation method and peak to peak method. The obtained velocity value was the average velocity between the nearest stations observations in the same river. While the correlation analysis used linear regression method. From the calculation of the lahars flow velocity, estimation of arrival time of lahars flow to nearest settlement was calculated. Estimated arrival time of Kali Boyong lahars flow to the nearest population based on correlation method was 10 - 23 minutes and based on peak-to-peak method was 10 - 29 minutes. Whereas, estimated arrival time of lahars flow in Kali Putih for 3 - 4 minutes and Kali Senowo about 2 minutes from that methods.